Stimulating Innovation in Russia The Role of Institutions and Policies - Gianella, Christian (OECD Publishing, 2007)
This paper examines the potential role of innovation policy in enhancing long-term productivity growth in Russia. It begins by exploring the role of framework conditions for business in encouraging innovative activities, particularly with respect to intellectual property rights and competition. Realising Russia's innovation potential will also require reform of the large public science sector. This raises issues pertaining to the organisation and financing of public research bodies and, in particular, to the incentives and opportunities they face in commercialising the results of their research. Finally, the paper looks at the potential role of direct interventions, such as special economic zones and technoparks, as well as the scope for improving the tax regime for private-sector R&D.
Keywords: Economics; Russian Federation